REDUCTION OF SOME HEAVY ELEMENTS FROM POLLUTED WATER USING THE BIOLOGICAL ADSORPTION TECHNQUE BY DRY ALGAE - & et al., Al-Qaisi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The biological adsorption technique was used with the powder of (Chara virgata, Cladophora  fuebllornei) algae with a dry weight of 0.5 g to treat water contaminated with heavy elements of lead, cadmium, copper, chromium and iron at the two following different locations in Baghdad: Al- Waziriyah Batteries factory, and Tanning & Leather Factory. The experiments were performed at a pH 6 and at a speed of 100 rpm in an electric vibrator. The chara virgata showed high removal ratios 100% of lead, cadmium, and iron respectively in the first half hour of the experiment, while the chromium and copper removal rates ranged from 74.6-100%, 73.2-100% with 0.5-3 hour treatment time respectively. The results of Cladophora fuebllornii were different for the chromium element with removal rates ranging from 77.7-100% and with a treatment time of 0.5-2 hours respectively .Copper removal rates ranged between 83.6-100% and 0.5-1.5 hours. Lead, cadmium, and iron also had 100% removal rates, respectively within the first half hour of the experiment. The analysis of the infrared device (FTIR) for the sample of the two-algae used in the experiments proved the presence of the active groups in the cellular walls of each alga, namely carboxyl, hydroxyl, alkyl, amine, and amide groups, which are responsible for bonding heavy element that present in the polluted water.